ЛЕКСИЧЕСКИЙ МИНИМУМ КАК СРЕДСТВО ОБУЧЕНИЯ РЕЧЕВОЙ КОММУНИКАЦИИ В СФЕРЕ ПРОФЕССИОНАЛЬНОГО ОБЩЕНИЯ - Сейтенова, В.А. (SCIENCE and SOCIETY, 2024)
In article consider the lexical contents of the education the Russian language student’s economic professions. The choice of theme is dictated by the necessity of education to the professionally business communication in the Russian language of the specialists in the field of commercial activity. The Principles of the choosing of the linguistically contents determined the criteria of the making up lexical contents. The material researched by the author, can become a linguistic basis for working out of the methodical system of the development of skills of professional speech in the Russian language of future economists. Selected the lexical minimum will can become a linguistic basis of the scholastic allowance in the Russian language for broad circle of the businessman’s, bound by business relations with Russia and other countries.
Keywords: the language for Specific Purposes; the communicative competence; business dialogue; basic word stock; the language maintenance of training; sphere of communication; criteria of the description; thematic efficiency; semantics; economic terminology; lexeme; set phrase